2017
DOI: 10.18632/oncotarget.21681
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic landscape change analysis during human EMT sheds light on a key EMT mediator TRIM29

Abstract: Epithelial to mesenchymal transition (EMT) is a key trans-differentiation process, which plays a critical role in physiology and pathology. Although gene expression changes in EMT have been scrutinized, study of epigenome is in its infancy. To understand epigenetic changes during TWIST-driven EMT, we used the AcceSssIble assay to study DNA methylation and chromatin accessibility in human mammary epithelial cells (HMECs). The DNA methylation changes were found to have functional significance in EMT – i.e. methy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 46 publications
0
11
0
Order By: Relevance
“…Most experimental models require a dramatic change in the expression of epithelial and mesenchymal markers to confirm EMT: E-cadherin and occludins are the most commonly used markers for the epithelial trait and N-cadherin and vimentin for the mesenchymal trait [35, 36]. Recently, it has reported that the potential targets of TRIM29 are highly enriched in EMT-related cellular pathways, such as epidermal development, cellular differentiation, and cell junctions, suggesting that TRIM29 is a key mediator of EMT [37]. TRIM29 induced EMT and promoted migration and invasion in pancreatic and bladder cancer cells [19, 22].…”
Section: Discussionmentioning
confidence: 99%
“…Most experimental models require a dramatic change in the expression of epithelial and mesenchymal markers to confirm EMT: E-cadherin and occludins are the most commonly used markers for the epithelial trait and N-cadherin and vimentin for the mesenchymal trait [35, 36]. Recently, it has reported that the potential targets of TRIM29 are highly enriched in EMT-related cellular pathways, such as epidermal development, cellular differentiation, and cell junctions, suggesting that TRIM29 is a key mediator of EMT [37]. TRIM29 induced EMT and promoted migration and invasion in pancreatic and bladder cancer cells [19, 22].…”
Section: Discussionmentioning
confidence: 99%
“…To date, TRIM29 has been reported to be positively or negatively involved in epithelial-mesenchymal transition (EMT) in cancers (10,36). RNAi-mediated gene knockdown of TRIM29 in breast cancer cell lines increases the expression of mesenchymal markers (N-cadherin and vimentin), decreases the expression of epithelial markers (E-cadherin), and increases the expression of the oncogenic transcriptional factor TWIST1, which is a key driver of EMT (10).…”
Section: Discussionmentioning
confidence: 99%
“…RNAi-mediated gene knockdown of TRIM29 in breast cancer cell lines increases the expression of mesenchymal markers (N-cadherin and vimentin), decreases the expression of epithelial markers (E-cadherin), and increases the expression of the oncogenic transcriptional factor TWIST1, which is a key driver of EMT (10). Another study used epigenetic change analysis to identify TRIM29 as a driver candidate during EMT (36). Furthermore, experimental model mice have revealed that TRIM29 facilitates EMT in pancreatic cancer cells (9).…”
Section: Discussionmentioning
confidence: 99%
“…EMT is one of the main mechanisms fuelling the tumour plasticity and heterogeneity and entails dynamic changes in transcriptional and epigenetic landscapes ( Figure 1 ) [ 12 , 93 ]. Studying EMT in normal and transformed cells indicates dependency on global epigenetic reprograming, that starts with extracellular cytokine or the induction of EMT master regulators (e.g., TWIST and SNAIL ).…”
Section: Enhancer Dynamics and Tumour Plasticitymentioning
confidence: 99%